THERAPEUTIC PROGRESS IN SYSTEMIC TREATMENT OF MODERATE-TO-SEVERE ATOPIC DERMATITIS - Aleksandra Jaskulska; Dominika Błonka; Jan Pietrzak; Magda Skudzińska; Karolina Wołk; Janina Pohrybieniuk; Filip Kochański; Maria Irena Grys; Magdalena Bartold; Kamil Rajczyk (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Atopic dermatitis (AD) is the most prevalent inflammatory skin disease characterized by severe pruritus, eczematous lesions, and impaired skin barrier function. Both pediatric and adult populations respond to it with considerable impairment in quality of life and psychosocial well-being. Until recently, treatment options were mostly non-specific, low in efficacy, and often with serious side effects, particularly in moderate to severe cases. Nonetheless, recent advances in understanding AD pathophysiology have led to development of biologics and small molecules that target molecular pathways in the immune system modifying disease processes. The first biologic approved for AD (dupilumab) emerged in 2017 and greatly improved disease outcomes paving the way for further novel therapies.Aim of study: The objective of this review is to summarize current and evolving systemic therapies for moderate to severe atopic dermatitis, particularly biologics and Janus kinase inhibitors. We summarize key clinical trial data, compare efficacy and safety profiles of approved agents and suggest future avenues for directed therapeutic approaches.Materials and Methods: The literature available in the PubMed database was reviewed using the following keywords:“Atopic dermatitis”, “abrocitinib”, “baricitinib”, “monoclonal antibodies”, “dupilumab”, “Janus kinase inhibitor”, “lebrikizumab”, “nemolizumab”, “tralokinumab”, “upadacitinib”.Summary: The development of tailored therapeutic strategies for these patients poorly controlled by traditional therapeutics is a result of advancement in AD pathophysiology. These innovations have shown considerable efficacy in reducing disease burdens and improving quality of life, serving as a paradigm shift in the current clinical care landscape.